Produksi, Karakteristik, dan Aplikasi Nanomaterial Fullerena - Ridhoi, Muhammad Fachmi; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2026)
This review provides an in-depth exploration of C60 fullerene-based polymers and their synthetic approaches, structural properties, and applications across various scientific fields, including material science, biomedicine, and nanotechnology. Starting from foundational developments in the synthesis of fullerenes, the review details the structural diversity of fullerene-based polymers, from cross-linked and end-capped polymers to more complex architectures such as star-shaped and side-chain polymers. It also discusses characterization techniques such as TEM, SEM, AFM, and DLS for assessing particle size, morphology, and distribution. Recent advancements in photovoltaic applications and supramolecular assemblies of fullerene-containing polymers illustrate the versatile applications of these materials. The review concludes with a discussion of fullerene’s potential in various applications, from cosmetics and gas adsorption to biomedical applications like drug delivery, antioxidant therapies, and diagnostics.